A study of safety factor in the design of passenger cars and motorcycles / Rizal Sharil Zabri - Zabri, Rizal Sharil (1999)
This work deals with a study on Safety Factors In Design Of Cars And Motorcycles. Case studies on safety factors in design of vehicles like cars and motorcycles are reported. All the information about safety factor is collected in detail. Every aspect in designs of passenger car and motorcycles are studied to find the drawback in the existing vehicles. And also to suggest suitable changes to improve the new design of cars and motorcycles in the future. This includes tips on how to avoid an accident, which is very important. Tips are also given on how to control and handle passenger cars and motorcycles.